Degenerate Four-Wave Mixing in Phycoerythrin Dye-Doped Nanoparticles - Tsuchiya, Tomoki; Egami, Chikara (International Journal of Optics, 2021)
We have generated a phase-conjugate (PC) wave from nanoparticles with a new microscopic system proposed. The microscope includes a confocal system with a degenerate four-wave mixing (DFWM) system, which plays a major role in generating the phase-conjugate wave to compensate phase distortion in the optical path toward targets. The proposed optical system detects feeble PC wave and imagines 3D particles while improving the inplane contrast resolution of the microscopic image.